HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP KESEHATAN GIGI DENGAN PENGALAMAN KARIES PADA ANAK SEKOLAH MINGGU KELAS 3-4 DI GEREJA HKBP TASIKMALAYA - Ruth, Sendy; Kusmana, Aan; Triyanto, Rudi (Jurnal Ilmiah Keperawatan Gigi, 2024)
Knowledge and attitude towards dental health is a very important role in shaping a person's actions in an effort to maintain healthy teeth and mouth, so that they are free from caries. The purpose of the studywas to determine the relationship between knowledge and attitudes towards dental healthwith caries experience in grades 3-4 at HKBP Tasikmalaya Church. Research methods using Cross sectional with descriptive analytics. The population of all grade 3-4 childrenamounted to 30 children with total sampling technique. Measurement tools usingquestionnaires DMFT examination formats. Data were analyzed using Chi-squarestatistical test. The results showed that the majority of grade 3-4 knowledge was inthemoderate category (63%), the attitude of grade 3-4 was in the moderate category (57%), and the caries experience index deft was in the moderate category (43%) while DMFTwas in the very low category (60%). The Chi Square test results show that there is arelationship between dental health knowledge and attitudes with caries experience ingrade 3-4 children at HKBP Tasikamalaya church with a p-value of knowledge withcaries experience of 0.000 < 0.05 and attitude with caries experience of 0.050